Pengaruh 2,4-D terhadap Induksi Kalus Daun Stroberi (Fragaria sp.) dengan Media Alternatif Nutrisi Hidroponik AB Mix - AJENG IDVATUL FITROH; RINDANG DWIYANI; I KETUT ARSA WIJAYA; HESTIN YUSWANTI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Influence of 2,4-D to induce callus from strawberry leaves on alternative media of AB Mix hydroponic nutrientThis research was conducted to find out the most optimum 2,4-D concentration to induce callus from strawberry leaves on alternative media of AB Mix hydroponic nutrient. This research used Completely Randomized Design with 5 levels of treatment concentration of 2.4-D hormon, first: AB Mix hydroponic nutrients (as basic media) without 2,4-D, second: basic media + 0.5 ppm 2.4 -D, third: basic media + 1 ppm 2,4-D, fourth: basic media + 1.5 ppm 2,4-D, fifth: basic media + 2 ppm 2,4-D. The variables observed were the day explant curled up, day explant swelled, percentage of eksplan curled up (%), percentage of explants swelled (%), the day callus appears, and percentage of explant browning (%). The best percentage of the treatment in callus induction of the strawberry leaves is on the P3 treatment with the concentration of 2,4-D as much as 1.5 ppm, with the fastest curled up explants time of 3 days after culture, the highest curled up eksplants (93.3%), the fastest swelled explants (17.0 days after culture), and the highest swelled percentage (40.0%). Callus formed 32 days after swelling. Successful callus formed only in treatment basic media with 1,5 ppm 2,4-D concentration.